2017
DOI: 10.1111/ijd.13798
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal observational study of hidradenitis suppurativa: impact of surgical intervention with adjunctive biologic therapy

Abstract: In this diverse cohort of patients with severe HS, biologic therapy was associated with a more rapid decline in disease activity, with the greatest effect in patients who also underwent HS surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 39 publications
1
32
0
4
Order By: Relevance
“…Our case confirms that the treatment approach in patients affected by advanced HS and progressive lymphedema needs to be individualized based on the association of biologic therapy and surgery to restore normal anatomy and function of the organ involved 2 . However, timing needs to be better defined, and clinical trials evaluating effectiveness of biological agents combined with surgery are needed 10 . Early detection of HS-associated lymphedema is crucial, and a multidisciplinary approach is fundamental 2 …”
Section: Discussionsupporting
confidence: 55%
“…Our case confirms that the treatment approach in patients affected by advanced HS and progressive lymphedema needs to be individualized based on the association of biologic therapy and surgery to restore normal anatomy and function of the organ involved 2 . However, timing needs to be better defined, and clinical trials evaluating effectiveness of biological agents combined with surgery are needed 10 . Early detection of HS-associated lymphedema is crucial, and a multidisciplinary approach is fundamental 2 …”
Section: Discussionsupporting
confidence: 55%
“…The majority ( n = 11) of these studies reported on the use of antibiotics and biologic medications, with only two mentioning retinoids [ 47 , 62 ]. Of these, one study discussed post-surgical use of biologics [ 18 ], four studies detailed use of biologics and antibiotics in the weeks or months preceding surgery [ 37 , 39 , 56 , 63 ], three detailed antibiotic and/or biologic use both pre- and post-surgical intervention [ 41 , 46 , 64 ], one detailed intraoperative use of a gentamicin sponge [ 11 ], and two studies did not specify exact timing [ 47 , 54 ]. Prens et al [ 46 ] reported significantly longer healing times with the use of adalimumab (five patients) and infliximab (one patient) started several months before surgery, held for 1–2 weeks perioperatively, and then re-instated postoperatively within 1–2 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who underwent surgery while on a biologic drug had better disease control than those who only had medical treatment in a study with 68 cases of moderate to severe HS. 142…”
Section: Surgical Treatmentmentioning
confidence: 99%